Accountability and satisfaction: organizational support as a moderator. Issue 5 (8th July 2014) - Wikhamn, Wajda; T. Hall, Angela
Abstract : Purpose: – The purpose of this paper is to investigate how perceived organizational support (POS) moderates accountability's relationship with job satisfaction. Design/methodology/approach: – Self-report data were collected from one organizational sample from the USA and one organizational sample from Sweden. Findings: – The results support the hypothesis that POS moderates the relationship between accountability and job satisfaction in the two samples. Specifically, the findings show that accountability relates positively to satisfaction under high support conditions and, in one sample, negatively to satisfaction under low support condition. Research limitations/implications: – The current results suggest that social context is vital to a more informed evaluation of how accountability relates to work outcomes. Organizations should show their employees that they care about them. This can be achieved through starting, maintaining, and nurturing those initiatives that are interpreted positively by the employees. Social implications: – Scandals represent examples of accountability failures. The implications of these scandals are not merely limited to individual companies and their employees. The wellbeing of the employees is part of the wellbeing of the society. Originality/value: – This study offers new insights on the relationship between accountability and job satisfaction. First, it demonstrates how organizational support perception functions as a moderator of this relationship. Second, it reports replicable results from two organizational samples – one from North America and one from Europe.